Peningkatan Hasil Belajar Matematika dalam Menyelesaikan Soal Bilangan Perkalian dan Pembagian di Kelas II SD - Nurdeni Nurdeni (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2011)
The objectives of the research are to improve the mathematics learning result in finishing the multiplication and division questions through contextual approach at grade II SDN Cempaka Baru 09 Jakarta. To be the further data to search another strategy or approach and to be the fundamental for the following research. The research was treated to 27 students of grade II at SDN Cempaka Baru in academic year 2009/2010 where they have to finish the multiplication and division questions. The research finding shows that there is a significance improvement of the students learning result in finishing the multipilication and division questions at grade II SDN Cempaka Baru 09 Jakarta Pusat. The percentage of step 1 is 61,3%, step II is 71,5%, and step III is 77,1%. Meanwhile, the percentage of contextual learning process of step I is 82,5%, step II is 89,5%, and step III is 93%. The correlation between the teaching and learning result and the contextually teaching and learning process is the more effective the contextual teaching and learning process, the higher scores of the students will be.